THE EFFECT OF VARIATIONS IN THE CONCENTRATION SORBITOL AND CASSAVA LIQUID SUGAR (Manihot esculenta Crantz) OF SWEETENER ON THE PHYSICAL PROPERTIES OF GUMMY CANDIES PARACETAMOL - Dewi - Rashati (AKADEMI FARMASI JEMBER, 2021)
Gummy candies paracetamol is chew candy containing the active subtance paracetamol with sweetener of sorbitol and cassava liquid sugar. The purpose of this study was to determine the effect of variations in the concentration of sorbitol and cassava liquid sugar as sweeteners on the physical properties of gummy candies paracetamol. Formulation of paracetamol gummy candies using diference concentration of sorbitol (20%, 15%, 10%) and cassava liquid sugar (40%, 45%, 50%).was used as the method pre-experimental design research method with one-shot case study design. Testing the physical properties of the preparations that have become chewing gum includes organoleptic tests, weight uniformity tests, pH tests and then the results are compared with the requirements in the literature. The results of the research on the physical properties of paracetamol gummy candy concluded that variations in the concentration of sorbitol sweetener and cassava liquid sugar had an effect on the uniformity of weight. Variations in the concentration of sorbitol sweetener and cassava liquid sugar did not affect the physical organoleptic properties of aroma, color, taste, texture, and physical properties of pH.Keywords : paracetamol, gummy candies, sorbitol, cassava liquid sugar